SI‐CLP inhibits the growth of mouse mammary adenocarcinoma by preventing recruitment of tumor‐associated macrophages. Issue 5 (4th December 2019) - Yin, Shuiping; Wang, Nan; Riabov, Vladimir; Mossel, Dieuwertje M.; Larionova, Irina; Schledzewski, Kai; Trofimova, Olga; Sevastyanova, Tatyana; Zajakina, Anna; Schmuttermaier, Christina; Gratchev, Alexei; Flatley, Andrew; et al.
Abstract : Chitinase‐like proteins (CLP) are chitin‐binding proteins that lack chitin hydrolyzing activity, but possess cytokine‐like and growth factor‐like properties, and play crucial role in intercellular crosstalk. Both human and mice express two members of CLP family: YKL‐40 and stabilin‐1 interacting chitinase‐like protein (SI‐CLP). Despite numerous reports indicating the role of YKL‐40 in the support of angiogenesis, tumor cell proliferation, invasion and metastasis, the role of its structurally related protein SI‐CLP in cancer was not reported. Using gain‐of‐function approach, we demonstrate in the current study that the expression of recombinant SI‐CLP in mouse TS/A mammary adenocarcinoma cells results in significant and persistent inhibition of in vivo tumor growth. Using quantitative immunohistochemistry, we show that on the cellular level this phenomenon is associated with reduced infiltration of tumor‐associated macrophages (TAMs), CD4+ and FoxP3+ cells in SI‐CLP expressing tumors. Gene expression analysis in TAM isolated from SI‐CLP‐expressing and control tumors demonstrated that SI‐CLP does not affect macrophage phenotype. However, SI‐CLP significantly inhibited migration of murine bone‐marrow derived macrophages and human primary monocytes toward monocyte‐recruiting chemokine CCL2 produced in the tumor microenvironment (TME). Mechanistically, SI‐CLP did not affect CCL2/CCR2 interaction, but suppressed cytoskeletal rearrangements in response to CCL2. Altogether, our data indicate that SI‐CLP functions as a tumor growth inhibitor in mouse breast cancer by altering cellular composition of TME and blocking cytokine‐induced TAM recruitment. Taking into consideration weak to absent expression of SI‐CLP in human breast cancer, it can be considered as a therapeutic protein to block TAM‐mediated support of breast tumor growth. Abstract : What's new? Chitinase‐like proteins possess cytokine‐like properties and can manipulate cancer progression. Here the authors show that stabilin‐1 interacting chitinase‐like protein (SI‐CLP) inhibits the growth of murine mammary adenocarcinoma by altering the tumor microenvironment and reducing intratumoral macrophage infiltration. SI‐CLP is weakly expressed in human breast cancers and may function as a possible therapeutic agent to suppress breast cancer growth.